Utilization and outcomes of rotational atherectomy in Sweden. (25th November 2020) - Venetsanos, D; Erlinge, D; Omerovic, E; Calais, F; Angeras, O; Jensen, J; Henareh, L; Todt, T; Gotberg, M; Sarno, G; Aasa, M; Lagerqvist, B; et al.
Abstract: Aim: To evaluate utilization and outcomes of rotational atherectomy (RA) using data from the Swedish Coronary and Angioplasty Registry (SCAAR) Methods: We included 1476 patients with 2218 lesions who underwent RA from 2005 to 2016. To study temporal changes, the study period was divided into three equal time-periods, period A, B and C. Results: Although the number of RA procedures increased 3-fold from 2005 to 2016, the rate of RA (of all PCI procedures) remained low (0.5% vs 1.2% in 2005 vs 2016). RA patients consisted a high-risk group, with advanced age and clustering of comorbidities. Over time, included patients were older and had a higher risk profile. Trans-radial access, drug eluting stent (DES) use and use of intravascular imaging significantly increased from period A to C whereas positioning of a temporary pacemaker or intra-aortic balloon pump declined. Unfractionated heparin became the main anticoagulant (52 vs 87%) and use of glycoprotein IIb/IIIa inhibitors declined (31 vs 12%, in period A vs C). Following RA, 11% of lesions were treated without stent (15 vs 15 vs 8%, in period A, B and C) (Rota-only). In lesions treated with a stent, a bare metal stent (BMS) was implanted in 39% vs 12% vs 2% and a new generation DES (N-DES) in 5 vs 75 vs 97% (period A vs B vs C) of lesions. The 3-year cumulative rate of restenosis was 6.7% (122 events), (11.1 vs 7.1 vs 4.1% in period A vs B vs C). As compared to DES, rota-only (adjusted HR 2.71; 95% CI 1.69- 4.36) and BMS (adjusted HR 3.63; 95% CI 2.27- 5.81) were associated with significantly higher risk for restenosis. First generation DES were associated with numerically higher but not significantly different risk for restenosis as compared to N-DES (adjusted HR 1.31; 95% CI 0.74- 2.31). The 3 year cumulative rate of major adverse cardiac events (MACE), including death, myocardial infarction (MI) or any restenosis was 30.6% (34.2 vs 31.4 vs 28.2%, in period A vs B vs C) and the corresponding numbers for all-cause mortality were 18.1% (18.9 vs 18.4 vs 17.0%). After adjustment for baseline characteristics and angiographic findings, RA in period A was associated with higher risk for MACE as compared to period C (adjusted HR 1.40; 95% CI 1.09- 1.79), due to higher risk for MI and restenosis. The difference disappeared when procedural characteristics, including DES use, were added to the model. The rate of major in-hospital complications was 7.0%, including in-hospital death 1.3%, periprocedural MI 2.8%, perforation 1.1%, cardiac tamponade 0.7%, stroke 0.2% and major bleedings 2.1%. We found no significant differences over time. Conclusion: During the studied period, RA remained a rare procedure, utilised in a highly selected population. Over time a declining rate of restenosis and MI after RA was observed, a finding that appeared to be mainly driven by an increased use of DES. The rate of major in-hospital complication remained low. Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): Boston Scientific International